The Effect of Work Motivation on Work Productivity of Women, Children, Population and Family Empowerment Services Services with Work Discipline as Intervening Variables - Syamsul Bahri; Vina Winda Sari (Jurnal Mantik, 2021)
This study has the following results, it can be seen that tcount (2.452) > ttable (2.042), as well as the significance value of 0.021 <0.05, it can be concluded that the first hypothesis is accepted, meaning that the work motivation variable (X) has a positive and significant effect on discipline. Work (Z). Second, it can be seen that tcount (3.219) > ttable (2.042), and the significance value is 0.003 <0.05, it can be concluded that the second hypothesis is accepted, meaning that work motivation (X) has a positive and significant effect on work productivity (Y). Third, it can be seen that tcount (4.711) > ttable (2.042), and the significance value is 0.000 <0.05, so it can be concluded that the third hypothesis is accepted, meaning that Work Discipline (Z) has a positive and significant effect on Work Productivity (Y). Path analysis shows the direct effect of variable X on variable Y of 0.392. Meanwhile, the indirect effect through the Z variable is 0.421 x 0.573 = 0.2412. From the calculation results obtained, the indirect effect through the Z variable is greater than the direct effect on the Y variable.